Bone morphogenetic protein 10: a novel risk marker of ischaemic stroke in patients with atrial fibrillation. (16th November 2022) - Hijazi, Ziad; Benz, Alexander P; Lindbäck, Johan; Alexander, John H; Connolly, Stuart J; Eikelboom, John W; Granger, Christopher B; Kastner, Peter; Lopes, Renato D; Ziegler, André; Oldgren, Jonas; Siegbahn, Agneta; et al.
Abstract: Aims: Biomarkers specifically related to atrial tissue may increase the understanding of the pathophysiology of atrial fibrillation (AF) and further improve risk prediction in this setting. Bone morphogenetic protein 10 (BMP10) is a protein expressed in the atrial myocardium. We evaluated the association between BMP10 and the risk of ischaemic stroke and other cardiovascular events in large cohorts of patients with AF, treated with and without oral anticoagulation (OAC). Methods and results: BMP10 was measured in plasma samples collected at randomisation in patients with AF without OAC in the ACTIVE A and AVERROES trials ( n = 2974), and with OAC in the ARISTOTLE trial ( n = 13 079). BMP10 was analysed with a prototype Elecsys immunoassay. Associations with outcomes were evaluated by Cox-regression models adjusted for clinical characteristics, kidney function, and N -terminal pro-B-type natriuretic peptide (NT-proBNP). Median concentrations of BMP10 were 2.47 and 2.44 ng/mL, in the non-OAC and OAC cohort, respectively. Increasing BMP10 was associated with lower body mass index, older age, female sex, kidney dysfunction, and AF rhythm. BMP10 was consistently associated with ischaemic stroke. In the non-OAC cohort, BMP10 increased the concordance index of the multivariable model from 0.713 to 0.733 ( P = 0.004) and in the OAC cohort from 0.673 to 0.694 ( P < 0.001). Additionally, BMP10 maintained a significant prognostic value after additionally adjusting for NT-proBNP. BMP10 was not independently associated with bleeding or with death. Conclusion: The novel atrial biomarker BMP10 was independently associated with ischaemic stroke in patients with AF irrespective of OAC treatment. BMP10 seems to be more specifically related to the risk of ischaemic stroke in AF. One-sentence Summary: In this study, BMP10 may be a novel specific biomarker of ischaemic stroke in patients with atrial fibrillation, irrespective of oral anticoagulation. Structured Graphical Abstract: Structured Graphical Abstract